Implementation Of Railway Doors Using Vibration Sensors And Ultrasonic Sensors Based On Arduino Uno - Muhammad Syahputra Novelan; Uc Mariance (Sean Institute, 2022)
In this study the tool used is in the form of a miniature as an implementation of automatic railroad doors to facilitate work in operating railroad doors which currently still require a lot of staff so that errors often occur due to negligence in operating which causes accidents on railroad crossings. fire. In this study, it will be designed using a motion sensor to detect the movement of a train if it is running and an ultrasonic sensor to measure the distance of a train whether it is approaching the railroad crossing. How the tool works is made by utilizing Arduino Uno and ultrasonic sensors as data input providers